The way of enforcing the cultural rights of prisoners in the Polish and Hungarian prisons: the aspects of creativity - Márta Miklósi; Daria Becker-Pestka; Attila Károly Molnár (Creativity Studies, 2023)
Education in Polish and Hungarian penitentiaries aims at the successful social reintegration of prisoners. Penitentiary institutions support prisoners by education of primary, secondary, and vocational training. Forms of learning within prisons prepare prisoners for release and integration into the labour market. This study aims to review the most important concepts and possible interpretations of criminal pedagogy and the cultural life of prisons. We present the main cultural rights of prisoners (learning opportunities, community cultural opportunities) and their impact on prisoners, as well as highlighting the aspects that make prison a total institution. We present the goals of cultural life in prison and the current training process covering key areas. We state that cultural activities in prison are essential parts of reintegration, bringing prisoners closer to the cultural nature of the outside world. With this article, comparatively on the two countries, we would like to draw attention to the diversity and feasibility of cultural transmission for prisoners.